Plasma rico em plaquetas homólogo injetável associado ou não com ômega 3 oral no tratamento da ceratoconjuntivite seca em cães - Villa, William dos Santos (2023)
Keratoconjunctivitis sicca (KCS) is a chronic inflammatory ophthalmopathy with a high incidence in dogs. Platelet-rich plasma (PRP) is rich in bioactive proteins that have tissue regenerating action and omega 3 (ω-3) is an essential fatty acid that has anti-inflammatory action. The aim of this study was to compare the use of injectable homologous platelet-rich plasma (PHRP) with or without oral omega 3 in dogs with CCS. We evaluated 22 dogs with bilateral CCS (44 eyes), with no racial, age or sexual predilection, randomly divided into 2 treatment groups with 22 eyes each: injectable homologous platelet-rich plasma (HPRP) group, and injectable HPRP group associated with ω -3 oral (HPRPO). In the HPRP and HPRPO groups, 0.1 ml of HPRP was administered via injection at each application point (lower and upper palpebral conjunctiva and in the third eyelid gland), once a month, totaling a maximum of three applications, according to the improvement of the signs of KCS, and the HPRHO group, in addition to the application of HPRP, was associated with oral ω-3 supplementation, 1 x/day, for 6 months. The animals were evaluated monthly for 6 months by clinical signs and specific ophthalmic tests: Schirmer's Tear Test-1 (STT-1), Tear Film Breakup Test (BUT), Fluorescein Test (TF). Regarding the number of PRP applications needed to improve signs of KCS, in the HPRP group (11 dogs) there were 3 applications (36%/4 dogs), 2 applications (55%/6 dogs), and one application (9% /1 dog) and in the PRPHO group (11 dogs) there were 3 applications (18%/2 dogs), 2 applications (55%/6 dogs), and one application (27%/3 dogs). In both treatment groups, ocular signs improved by the end of the study, and resolution of corneal ulcers was earlier in the HPRPO group. There was a significant increase (p < 0.05) in STT-1 and TBUT in both groups from M0 to M6, with no statistical difference (p > 0.05) between groups in STT-1, but in TBUT there was a more significant increase (p < 0.05) in HPRPO compared to HPRP from M3 to M6. It is concluded that both KCS treatment groups in dogs were effective in improving the clinical signs and in the quantitative and qualitative portion of the tear, but the PRPHO group was more effective in improving the quality of the tear, in earlier resolution of ulcers of cornea and reducing the number of HPRP applications, which shows the importance of associating oral ω-3 supplementation to improve the performance of regenerative cell therapy with injectable PRP in the treatment of CCS.